Pengembangan Video Animasi Berbantuan Media Renderforest Materi Pernapasan IPAS Kelas V SDN I Wonorejo - Lailatul Mubarokah Ramadhani; Nourma Oktaviarini (Departement of Mathematics Education, 2024)
The development of the times will provide many changes in human life, especially in the field of education, one of which is in the subject of IPAS subjects in elementary school. Lack of learning media for IPAS subjects learning media is still less supportive, this is the background of the researcher to raise the issue. The purpose of the media in the form of learning videos. It is hoped that students will be able to develop curiosity about environment. Renderforest rock animation video refers to an animated video made using the animation video created using the Renderforest platform. Methods this research uses the ADDIE model which consists of analysis, design, development, implementation and evaluation. The instruments used in this research is a questionnaire, interview, documentation. The results obtained from the results obtained from the media expert validation were 90% and the material expert obtained 91.2%. Assessment questionnaires and interviews were conducted with fifth grade students of SDN 1 Wonorejo, totaling 37 students. totaling 37 students. The results of this study indicate that the animated video media assisted by Renderforest breathing material learning IPAS class V SDN 1 Wonorejo is very valid to be used as an animated video media. 1 Wonorejo is very valid for use as learning media in the classroom. The results of This research can be applied with the video media used to make it easier for students to understand a material. Making it easier for students to understand a material.